Yayılı Temel BoyutlandırmadaYatak Katsayısı Kavramının Uygulanabilirliği - Bozkurt, İbrahim; AREL, ERSİN; ÖNALP, AKIN (My University, 2018)
Bildiride, yatak katsayısı kavramının yayılı temel boyutlandırılmasında ne denli uygulanabilir olduğu araştırılarak bu yöntemle yayılı temellerde hesaplanan oturmaların, doğrusal olmayan davranışı esas alan yöntemlerle arasındaki farklar irdelenmektedir. Bu amaçla; aynı sayısal problemlerin, yatak katsayısına dayalı Winkler, geliştirilmiş Vlasov yöntemiyle ve zemin ortamının sadece sürekli sonlu elemanlarla modellendiği doğrusal elastik ve doğrusal olmayan malzeme davranışını içeren analizleri yapılmıştır

Majority of software that enable the engineer to analyse raft foundations are based on the Winkler hypothesis. This paper gives an account of a study carried out to evaluate the feasibility of this historical approach in calculating the settlement and the deformation of plates and compares the results with those obtained by numerical methods based on nonlinear behaviour. The analyses were performed for a plate on layered soil using the Winkler method based on the coefficient of subgrade modulus as well as its improved version by Vlasov. The computation was subsequently repeated where the system was modelled by finite elements using linear elastic and non-linear soil-plate interaction. It is concluded that the two parameter Vlasov model should be preferred over the classical Winkler approach. The Vlasov method provides realistic results especially for soils with high rigidity suggesting that models using subgrade modulus concept should be avoided in loose and soft soils.
Keywords: Yatak Katsayısı; Yayılı Temel Boyutlandırma; Sonlu Elemanlar Yöntemi; Modulus of Subgrade Reaction; Raft Foundation Design; Finite Element Method